THE IMPORTANCE OF HUMANISTIC PSYCHOLOGY IN PROFESSIONAL PERSONALITY DEVELOPMENT AND IN ENHANCING PROCESSES OF PROFESSIONAL SELF-AWARENESS - Zamira Bakhtiyarovna Bilolova; Yulduz Erkinovna Kholova (Bright Mind Publishing, 2026)
This article explains scientific psychological theories that are important for professional personality formation and for developing processes of professional self-awareness, with particular emphasis on the significance of humanistic psychology. In addition, based on Abraham Maslow’s hierarchy of needs theory, the article outlines the key psychological mechanisms of professional development and professional self-awareness.
Keywords: Personality, professional formation, professional development, scientific psychological theories, A. Maslow, needs theory, motivation, professional self-awareness, self-actualization.